On the Role of Endothelial TRPC3 Channels in Endothelial Dysfunction and Cardiovascular Disease - Smedlund, K. (2012)
In endothelium, calcium (Ca(2+)) influx through plasma membrane Ca(2+)-permeable channels plays a fundamental role in several physiological functions and in the pathogenesis of cardiovascular disease. Current knowledge on the influence of Ca(2+) influx in signaling events associated to endothelial dysfunction has grown significantly over recent years, particularly after identification of members of the Transient Receptor Potential Canonical (TRPC) family of channel forming proteins as prominent mediators of Ca(2+) entry in endothelial cells. Among TRPC members TRPC3 has been at the center of many of these physiopathological processes. Progress in elucidating the mechanism/s underlying regulation of endothelial TRPC3 and characterization of signaling events downstream TRPC3 activation are of most importance to fully appreciate the role of this peculiar cation channel in cardiovascular disease and its potential use as a therapeutic target. In this updated review we focus on TRPC3 channels, revising and discussing current knowledge on channel expression and regulation in endothelium and the roles of TRPC3 in cardiovascular disease in relation to endothelial dysfunction.